Changes in N, K, and Fatty Acid Composition of Black Cumin Seeds Affected by Nitrogen Doses under Supplemental Potassium Application - Aytac, Zehra; Gulmezoglu, Nurdilek; Saglam, Tugce; Kulan, Engin Gokhan; Selengil, Ugur; Hoşgün, Halit Levent (Hindawi Ltd, 2017)
This study was carried out to determine the efficiency of nitrogen (N) doses (0, 30, 60, and 90 kg N ha(-1)) under supplemental potassium (K) application (50 kg K-2 O ha(-1)) on black cumin in 2011 and 2012. The results showed that increased N levels resulted in increasing seed yield and N and K contents in seed, while oil content decreased. The seed yield and oil yield were peaked at the doses of 60 kg N ha(-1) and 50 kg K ha(-1). An increase in N doses caused a reduction in oil content regardless of K supply. Saturated fatty acids and oleic acid were slightly increased by K application, while minor changes in linoleic acid were detected. It was concluded that 60 kg N ha(-1) with supplemental K application should be advised for enhancement in seed yield, oil yield, and N and K contents in seeds of black cumin without significant changes in fatty acid composition.
Keywords: [No Keywords]